Microwave-assisted green synthesis of nitrobenzene using sulfated natural zeolite as a potential solid acid catalyst - Saviola, Aldino Javier; Wijaya, Karna; Saputri, Wahyu Dita; Hauli, Latifah; Amin, Amalia Kurnia; Ismail, Hilda; Budhijanto, Budhijanto; Oh, Won Chun; Wangsa, Wangsa; Prastyo, Prastyo (Springer Science and Business Media Deutschland GmbH, 2023)
Natural zeolite and sulfated natural zeolite catalyst materials have been successfully prepared, characterized, and applied as a replacement for the role of a sulfuric acid catalyst in the synthesis of nitrobenzene. Natural zeolites were prepared into uniform-sized powders and then refluxed with H2SO4 with varying concentrations of 0, 1, 2, 3, and 4Â M, proceeded by calcination with N2 gas flow (labeled as NZ, SNZ-1, SNZ-2, SNZ-3, and SNZ-4). Nitrobenzene was synthesized in a batch microwave reactor using natural zeolite and sulfated natural zeolite catalysts with the best acidity value. The results showed that the sulfuric acid treatment of natural zeolite caused changes in its physical and chemical characteristics. The NZ catalyst has an acidity value of 1.742Â mmolÂ gâ1, and the 2Â M concentration variation resulted in the sulfated natural zeolite with the best acidity value of 1.625Â mmolÂ gâ1. The optimal amount of catalyst required is 1.0Â g. Both catalysts are selective toward the nitration reaction of benzene. The average benzene conversion produced for each catalyst was 41.53 Â± 3.61% and 58.92 Â± 1.37%. Furthermore, the SNZ-2 catalyst has better reusability for three reaction runs. Graphical abstract: Figure not available: see fulltext.